2021
DOI: 10.1002/hep.31855
|View full text |Cite
|
Sign up to set email alerts
|

Group‐2 Innate Lymphoid Cells Promote HCC Progression Through CXCL2‐Neutrophil‐Induced Immunosuppression

Abstract: Background & Aims: Due to their inherent characteristics, the function of group-2 innate lymphoid cells (ILC2s) varies in a context-dependent manner. ILC2s are involved in certain liver diseases; however, their involvement in hepatocellular carcinoma (HCC) is unknown. In the present study, we assessed the role of an HCC-derived ILC2 population in tumor progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 41 publications
1
56
0
Order By: Relevance
“…This was confirmed in a recent study by Xu et al. where the abundance of ILC2s in the tumor area of HCC patients liver is correlated with poor prognosis ( 62 ). When looking closely at the phenotype, they identified a subset of ILC2s, enriched in the tumor tissue but absent in the non-tumoral area, lacking the expression of killer cell lectin-like receptor subfamily G member 1 (KLRG1), a known marker for mature and activated ILC2s.…”
Section: Pro- and Anti-tumoral Roles Of Ilcs In Hccsupporting
confidence: 62%
See 2 more Smart Citations
“…This was confirmed in a recent study by Xu et al. where the abundance of ILC2s in the tumor area of HCC patients liver is correlated with poor prognosis ( 62 ). When looking closely at the phenotype, they identified a subset of ILC2s, enriched in the tumor tissue but absent in the non-tumoral area, lacking the expression of killer cell lectin-like receptor subfamily G member 1 (KLRG1), a known marker for mature and activated ILC2s.…”
Section: Pro- and Anti-tumoral Roles Of Ilcs In Hccsupporting
confidence: 62%
“…Co-cultures of murine hepatic ILC2s with Hepa1-6 cells resulted in significant decrease in KLRG1 levels. Hepa1-6 cells do not express E-cadherin but overexpression of its Cdh1 gene maintained KLRG1 expression in ILC2s ( 62 ). These experiments suggest that the loss of KLRG1 on ILC2s in HCC can be accounted for by a decrease in E-cadherin expression at the surface of hepatocytes.…”
Section: Pro- and Anti-tumoral Roles Of Ilcs In Hccmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown a role for ILC2s in both tumour promotion and tumour rejection, which have been comprehensively summarized elsewhere 57 . However, over the past 2 years, considerable progress has been made in the understanding of how specific populations of ILC2s contribute to immunosurveillance in different types of cancer 58 62 (Fig. 2 ).…”
Section: Ilc2s In Cancermentioning
confidence: 99%
“…Similarly, in another study, ILC2 infiltration was associated with better outcomes in patients with pancreatic ductal adenocarcinoma, and the antitumor function of ILC2s was found to be dependent on ILC2activating IL-33 (14). Conversely, another study showed that a higher infiltration of less-mature KLRG1 − ILC2 in HCC promoted tumor development, attributed to the possibility that ILC2s mediate immunosuppression in the tumor microenvironment through the KLRG1 − ILC2/ CXCL2/neutrophil pathway (15). The diverse functions of ILC2s on tumor regulation may be caused by multiple tumor types or by the influence of complicated cytokine networks.…”
Section: Editorialmentioning
confidence: 88%